Consumption of pork meat and its derivatives in the southeastern mesoregion of Pará in the period of the Covid-19 pandemic (Research, Society and Development, 2022)
Brazilian swine farming has grown in recent years with the use of technologies and greater knowledge in the areas of nutrition, management, genetics and animal welfare. Allied to this, there is a product with high nutritional value and excellent taste. In this sense, the objective of this work was to characterize the consumption of pork and other swine products in the region Southeast region of Pará during the pandemic. The research was carried out in the southeastern mesoregion of the state of Pará during 2021, to study the process of evaluating the opinion of the region's residents regarding pork consumption during the Covid-19 pandemic period, for this, a questionnaire was structured and elaborated on the Googleforms platform. The questionnaire was widely publicized and shared through social media. It was possible to observe that the frequency of consumption of pork and the purchase in supermarkets was 46% for both, while in relation to the choice of the most purchased pork cuts was the rib with 31%, having as a criterion better flavor. Of the interviewees, 58% use swine lard in cooking. Thus, it is extremely relevant strategies of the productive market for disclosures about the benefits and quality of Brazilian pork.